2012
DOI: 10.1111/j.1550-7408.2012.00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Sterol Composition and Biosynthetic Genes of the Recently Discovered Photosynthetic Alveolate, Chromera velia (Chromerida), a Close Relative of Apicomplexans

Abstract: Chromera velia is a recently discovered, photosynthetic, marine alveolate closely related to apicomplexan parasites, and more distantly to perkinsids and dinoflagellates. To date, there are no published studies on the sterols of C. velia. Because apicomplexans and perkinsids are not known to synthesize sterols de novo, but rather obtain them from their host organisms, our objective was to examine the composition of the sterols of C. velia to assess whether or not there is any commonality with dinoflagellates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…To date, despite the evolutionary importance of C. velia's plastid, there is a noticeable gap in knowledge of its lipid biochemistry, with only a single published study on the composition of C. velia's forms of MGDG and DGDG by Botté et al (2011) and a single published study on its sterol composition by Leblond et al (2012). In their recent study, Botté et al (2011) found major forms of MGDG and DGDG containing 20:5 at both the sn-1 and sn-2 positions, and minor forms containing 20:5 and 16:0 (regiochemistry undetermined).…”
Section: Introductionmentioning
confidence: 99%
“…To date, despite the evolutionary importance of C. velia's plastid, there is a noticeable gap in knowledge of its lipid biochemistry, with only a single published study on the composition of C. velia's forms of MGDG and DGDG by Botté et al (2011) and a single published study on its sterol composition by Leblond et al (2012). In their recent study, Botté et al (2011) found major forms of MGDG and DGDG containing 20:5 at both the sn-1 and sn-2 positions, and minor forms containing 20:5 and 16:0 (regiochemistry undetermined).…”
Section: Introductionmentioning
confidence: 99%
“…), however, synthesize a wide variety of sterols de novo (Patterson , ), which does not generally include those produced by C. velia and V. brassicaformis (see discussion by Leblond et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…24‐Ethylcholest‐5‐en‐3β‐ol is the predominant sterol in both V. brassicaformis and C. velia ; however, C. velia produces an additional array of sterols, namely 24‐methylcholesta‐5,22E‐dien‐3β‐ol and 24‐ethylcholesta‐5,22E‐dien‐3β‐ol, that are not found in V. brassicaformis but are commonly found in plant and other groups of algae but not in dinoflagellates (Leblond et al. ). Based on the KEGG reference pathway (Ogata et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The photosynthesis system of C. velia is highly efficient and adaptable to a range of light conditions owing to its specialised photoacclimation strategies (Kotabová et al ., ; Quigg et al ., ). Since its original isolation, published studies have cultured C. velia photoautotrophically in simple, inorganic growth media (Moore et al ., ; Guo et al ., ; Sutak et al ., ; Oborník et al ., ; Leblond et al ., ). Compared to the physical conditions, there has been relatively little exploration in terms of the nutritional factors of C. velia cultivation.…”
Section: Introductionmentioning
confidence: 99%